Is it time to revise the diagnostic criteria for apathy in brain disorders? The 2018 international consensus group - Robert, P. (2018)
Background: Apathy is a very common behavioural and psychological symptom across brain disorders. In the last decade, there have been considerable advances in research on apathy and motivation. It is thus important to revise the apathy diagnostic criteria published in 2009. The main objectives were to: a) revise the definition of apathy; b) update the list of apathy dimensions; c) operationalise the diagnostic criteria; and d) suggest appropriate assessment tools including new technologies. Methods: The expert panel (N = 23) included researchers and health care professionals working on brain disorders and apathy, a representative of a regulatory body, and a representative of the pharmaceutical industry. The revised diagnostic criteria for apathy were developed in a two-step process. First, following the standard Delphi methodology, the experts were asked to answer questions via web-survey in two rounds. Second, all the collected information was discussed on the occasion of the 26th European Congress of Psychiatry held in Nice (France). Results: Apathy was defined as a quantitative reduction of goal-directed activity in comparison to the patient's previous level of functioning (criterion A). Symptoms must persist for at least four weeks, and affect at least two of the three apathy dimensions (behaviour/cognition; emotion; social interaction; criterion B). Apathy should cause identifiable functional impairments (criterion C), and should not be fully explained by other factors, such as effects of a substance or major changes in the patient's environment (Criterion D). Conclusions: The new diagnostic criteria for apathy provide a clinical and scientific framework to increase the validity of apathy as a clinical construct. This should also help to pave the path for apathy in brain disorders to be an interventional target.